THE YOUNG PATIENT'S PERCEPTION REGARDING THE NEED FOR ORTHODONTICS TREATMENTS - Carina Balcoș; Daniela Argatu; Alexandru Lodbă; Eugenia Larisa Țarevici; Irina Bamboi; Hadad Clara; Anca Stupu Rapis; Carmen Savin; Oana Sorana Roșu; Adina Armencia (Romanian Dental Association for Education, 2022)
Malocclusion is the third most common dental public health problem worldwide. It is not regarded as a disease, but rather as a deviation from aesthetic standards. Aim: To evaluate the orthodontic status of the young adults from Iasi, to establish the need for orthodontic treatment and their perception regarding the aesthetic aspect of dento-maxillary anomalies. Material and methods: All individuals were clinically examined to determine the IOTN index. After completing the clinical examination, the participants were given a questionnaire that sought to obtain information related to the perception of their own facial aesthetics and the factors that influence access to specialized medical services. Results: From 187 subjects, only 22.5% need orthodontic treatments (10.7% - IOTN 3, IOTN 4 (6.4%) , IOTN 5 (5.3%)). Aesthetically, 81% of subjects were in the 1-4 IOTN AC group, while 66.7% of subjects with class II were in the "borderline" group 5-7. Only 36.4% consider their dental anomaly to be very serious, 32.1% of the participants want to improve the aesthetics of their smile and only 17.1% all the functions of the stomatognathic system. Conclusion: The need for orthodontic treatment is relatively low in the young population, with the main motivation being to improve the aesthetic aspect. From an aesthetic standpoint, the need for treatment is greater, with more than half of the participants classified as needing treatment.